Induced carotid atherosclerosis in lupus mice. (4th July 2019) - Wang, Yuehai; Huang, Ziyang; Lin, Ling; Huang, Guangyong; Liu, Weitao; Xue, Yuzeng
ABSTRACT: Fas knockout (Fas −/- ) mice are a model for systemic lupus erythematosus (SLE) -like autoimmune syndromes. We aimed to induce atherosclerosis (AS) inFas −/- mice. Sixteen male Fas −/- mice were included in the study, sex-matched C57B6/L (B6) and apolipoprotein E-knockout (ApoE −/- ) mice were negative and positive AS controls, respectively. A silica collar was placed around the right carotid artery of each mouse to induce AS development. All mice were fed a 24-week high-fat diet, and investigated for AS lesions. We also compared the levels of blood lipid and glucose, serum tumor necrosis factor α (TNF-α), interleukin 6 (IL-6), anti-nuclear antibody (ANA) and anti-double-stranded deoxyribonucleic acid (anti-dsDNA) antibody in Fas −/- mice with those in B6or ApoE −/- mice. All ApoE −/- and 6 Fas −/- but no B6 mice showedatherogenesis in right carotid artery . Thecarotid plaque contains more collagen and less lipid in Fas −/- than ApoE −/- mice. The levels ofblood glucose, serum TNF-α, IL-6, ANA, and anti-dsDNA antibody were significantly higher in Fas −/- mice than those in B6 mice, the levels of serum TNF-α and blood glucose were significantly higher and the level of blood lipid was significantly lower in Fas −/- mice than those in ApoE −/- mice . Therefore, carotid AS can develop in Fas −/- mice . Fas −/- mice display higher levels of serum IL-6, TNF-α, ANA, and anti-dsDNA than B6 mice, higher levels of serum TNF-α and blood glucose and lower level of blood lipid than ApoE −/- mice, andless lipid andmore collagen in ASplaque than ApoE −/- mice.